An experimental investigation into the behavior of premixed flames of hydrogen/carbon monoxide/air mixtures in a half-open duct. (1st February 2019) - Yang, Xufeng; Yu, Minggao; Zheng, Kai; Wan, Shaojie; Wang, Liang
Highlights: Premixed flame behavior of hydrogen/carbon monoxide/air mixtures is systematically investigated. The effect of PVC membrane on flame behavior has been examined. The distorted tulip flame in a half-open duct has been obtained and analyzed. The flame front can be stretched after flame skirt touched the sidewalls. The pressure waves cannot change the flame front structure. Abstract: In this paper, the premixed flame behavior of hydrogen/carbon monoxide/air mixtures is investigated experimentally in a half-open duct with a large aspect ratio ( L / D  = 20), employing a high-speed camera and a pressure transducer. The flame front structure, flame tip position, and flame tip velocity of the mixtures are obtained by analysing the high-speed images. Meanwhile, the overpressure history is obtained and analysed to examine their effects on the flame propagation behaviour. Additionally, the effects of the PVC membrane on the flame propagation behaviour is specifically scrutinized. The experimental results indicate that the effects of the PVC membrane on the flame front shape are negligible, but they can affect the flame tip and overpressure dynamics more or less in some specific conditions. When the flame propagates along the half-open duct, four stages of the tulip flame formation can be obtained in all cases. Additionally, the tulip distortion phenomenon occurs in most of the cases. This indicates that the distorted tulip flame may be an intrinsic and universal phenomenon. The most interesting phenomenon is that there is a flame front stretch process in the stage where the flame's skirt touches the sidewalls. This stretched process cannot affect the flame front inversion and tulip distortion. In this work, an observable oscillation in the overpressure history results from the changes in the flame's surface area. In addition, the flame stretch process indicates that the pressure waves cannot change the flame front structure. This is evidence that the pressure waves are not the incitation factor for the flame inversion and tulip distortion in the half-open duct.